The Influence of Accounting Information Systems, Information Quality, and Service Quality on User Satisfaction in the Shopee E-Commerce Application (Empirical Study on S1 Accounting Students at the Faculty of Economics and Business, Mulawarman University - Ardelia Hong Simarmata, Sonnia; Irwansyah, Irwansyah (International Journal of Educational Research & Social Sciences, 2024)
Sonnia Ardelia Hong Simarmata, The Effect of Accounting Information Systems, Information Quality and Service Quality on User Satisfaction in E-Commerce Shopee Application (Empirical Study on Undergraduate Students of Accounting Department, Faculty of Economics and Business, Mulawarman University), in the guidance of Mr. Irwansyah. The study's primary objective is to figure out what type of content Shopee brand app clients are. In our quest, we depend on the investigations undertaken by DeLone and McLean. Students from Mulawarman University's School of Business and Economics taking part. Using the Slovin method, the researchers settled upon a sample size of 91 for the study. In order to collect data from a stratified and unfiltered group of people, we utilized Google Forms questionnaires. As part of its mathematical modeling the method, the study used the SEM-PLS method and SmartPLS 3.2.9 programs. The Shopee e-commerce app's data shows that accounting information systems significantly and positively affect consumer happiness. Just like every other aspect of a product or service, information quality significantly impacts consumer satisfaction. Customer satisfaction with the Shopee e-commerce app is low regardless of the quality of service.